Chinese Calligraphy Inspired Design of Humidity/Light Dual Responsive Magic Paper. Issue 8 (3rd June 2021) - Gao, Jushan; Zhao, Xinxin; Wen, Jinpeng; Hu, Datao; Li, Ruilin; Wang, Ke
Abstract: Paper flowers are frequently, for example as indoor decorations and in wedding bouquets. But these traditional paper flowers can only maintain static conditions, greatly affecting their sensory effects, vividness, and appreciation. The design of novel paper flowers with dynamic shape deformation could effectively broaden the application of paper flowers. Here, inspired by Chinese calligraphy, a novel polyvinyl butyral (PVB)/carbon/cellulose composite (PCC) magic paper with a sandwiched structure is prepared. The hygroscopicity difference between hydrophobic PVB and hydrophilic cellulose layer endows the PCC paper with humidity responsiveness, and the maximum bending angle is up to 91.4° upon exposure to humidity environment. Carbon in the interlayer with strong light–heat conversion capacity could further accelerate water desorption and deformation speed, resulting in highly sensitive light responsiveness. The recovery time of PCC paper from maximum bending to the original flat state is shorter than 1 s. The PCC paper has good flexibility and processability, which can be cut and assembled into flowers with different shapes, and these unique magic flowers could freely bloom and furl upon external stimulus. All these results indicate that PCC paper has great potential in the production of magic props, artworks, and intelligent household decorations fields. Abstract : Inspired by Chinese calligraphy, a novel polyvinyl butyral (PVB)/carbon/cellulose composite (PCC) magic paper is prepared. The PCC paper has humidity/light dual responsiveness. When ambient moisture increases, the paper will bend toward PVB sides. When irradiated by NIR light, the paper bends toward the cellulose paper side. It can imitate the vivid blooming and furling process of flowers.